Everyday creativity - Ilha Villanova, Ana Luisa (2022)
We systematically review the concept and main characteristics of everyday creativity. First, we highlight the fact that a comprehensive definition of everyday creativity is still missing. The evidence reveals that the lack of a single approach for assessing everyday creative outcomes has led to an ambiguous understanding of this concept. Therefore, we propose a complementary perspective to define everyday creativity moving toward a broader comprehension of the construct. Second, we identify and analyze the main proprieties of everyday creativity in order to clearly distinguish it from big-c creativity, genius kind of creativity; thereby offering a more complete explanation of the concept. Last, we outline pathways for future research, emphasizing the potential of everyday creativity studies to intersect between multiple fields.